1984
DOI: 10.1002/hlca.19840670721
|View full text |Cite
|
Sign up to set email alerts
|

Preparation by yeast reduction and determination of the sense of chirality of enantiomerically pure ethyl (−)‐4,4,4‐trichloro‐3‐hydroxy‐ and (+)‐4,4,4‐trifluoro‐3‐hydroxybutanoate

Abstract: (Fig. 2 and 3).Enantiomerically pure 4,4,4-trichloro-and 4,4,4-trifluoro-3-hydroxybutanoic acid derivatives 1 and 2 are highly desirable chiral starting materials for organic synthesis. Thus, the p-lactone of (S)-4,4,4-trichloro-3-hydroxybutanoic acid was shown by Wynberg & Staring [I] to be accessible in 98% enantiomeric excess (ee) by quinidine-catalyzed asymmetric cycloaddition of ketene to chloral, and was hydrolyzed to (S)-malic acid, a source of numerous useful chiral building blocks [2]. In view of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…[15] This enzyme demonstrated the highest enantioselectivity observed for this bioreduction known thus far. [16] Bioreduction of 1 (20 mM) with resting cells of Bacillus pumilus Phe-C3 (6.7 g cdw/L, cdw ¼ cell dry weight) showed that the addition of 2% glucose increased the initial activity from 2.7 to 12 U/g cdw (U ¼ mmol/min) via the recycling of NADPH inside the cells. However, such cofactor recycling is not efficient, and biotransformation for 5 h yielded (R)-2 in only 42% yield.…”
mentioning
confidence: 99%
“…[15] This enzyme demonstrated the highest enantioselectivity observed for this bioreduction known thus far. [16] Bioreduction of 1 (20 mM) with resting cells of Bacillus pumilus Phe-C3 (6.7 g cdw/L, cdw ¼ cell dry weight) showed that the addition of 2% glucose increased the initial activity from 2.7 to 12 U/g cdw (U ¼ mmol/min) via the recycling of NADPH inside the cells. However, such cofactor recycling is not efficient, and biotransformation for 5 h yielded (R)-2 in only 42% yield.…”
mentioning
confidence: 99%
“…More generally, the difference in ideality of phase behavior can often be used to assign absolute configuration of a molecule if a close analogue of known configuration is available because the heterofacial (quasienantiomeric) combination of molecules almost always deviates more from ideality than the homofacial combination. [10] In a related method, cocrystallization of a pair of quasienantiomers, one of known absolute configuration and the other of unknown configuration, followed by X-ray crystallographic analysis of the quasiracemate can directly yield the absolute configuration of the unknown component. Again, the method is limited since the pair of compounds must yield suitable crystals.…”
Section: Quasienantiomers As Tools For Enantiomer Identification: Thementioning
confidence: 99%
“…Many β-keto esters possessing one or more heteroatoms containing moieties attached to C-4 have been reduced by baker's yeast, and the yeast-to-substrate ratio was found to be the most important parameter for obtaining good results [193,250,251,256,265,[276][277][278][279][280][281][282]. Yields and stereoselectivity were dropped for β-keto esters carrying an additional stereogenic center [283,284], and the reduction of α-thiosubstituted β-keto esters has been suggested as an alternative to the reduction of unsubstituted β-keto esters to improve yields and selectivity.…”
Section: Figure 2115mentioning
confidence: 99%
“…(E)-2-Alkyl-4,4,4-trichloro-2-butenals were regiospecifically converted to the corresponding saturated alcohols with high enantioselectivity, whereas the (Z)-isomers were reduced to afford allyl alcohols [472]. Polyfluorinated β-keto esters were efficiently reduced, and the products were usually obtained in good yields [276,278]. The reduction of 2-fluorocinnamyl alcohols by baker's yeast furnished (S)-2-fluoro-3-aryl-propanols in high yields with up to 92% ee [473].…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%